Evaluation of Professional Development Plan: Basis for School Development Program - Lauro , Julie Ann; Yaneza, Genefer; De Ungria, Celeste; Manalastas, Angelito (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study evaluated the implementation of the Professional Development Plan (PDP) at Lagundi-CCL National High School as a basis for enhancing the School Development Program (SDP). Anchored on the policies of the Department of Education, particularly DepEd Order No. 42, s. 2017, the research emphasized the role of continuous professional development in improving teacher quality and student outcomes. Using a mixed-methods approach, the study combined descriptive-quantitative analysis and thematic qualitative techniques to gather comprehensive insights from thirty-one (31) teacher-participants. Data were collected through a researcher-made survey questionnaire and in-depth interviews.Findings revealed that while the PDP was generally assessed as “Agree” in terms of goal setting, relevance, and engagement, several critical gaps remain. Teachers reported a lack of alignment between PDP goals and actual classroom responsibilities, limited opportunities for application and reflection, and insufficient feedback mechanisms. Thematic analysis further identified key challenges, including unclear goal alignment, low motivation due to non-contextualized training, and inadequate structural support such as mentoring and coaching. Issues on customization and practical application also emerged, highlighting the need for more responsive and teacher-driven PDP designs. Based on these findings, the study proposed an action plan focused on needs-based training, increased teacher participation, strengthened mentoring systems, and integration of PDP initiatives into the SDP and School Improvement Plan (SIP). The study concludes that while PDP implementation demonstrates foundational strengths, its effectiveness can be significantly enhanced through contextualization, collaboration, and sustained support mechanisms. Ultimately, a responsive and data-driven PDP can serve as a strategic tool in advancing both teacher development and overall school performance.
Keywords: Professional Development Plan, teacher development, school development program, PDP evaluation, DepEd, educational improvement